The seed industry in Vietnam - Dung, Nguyen Mau (International Food Policy Research Institute, 2014)
For the last three decades, Vietnam’s agricultural sector has undergone continuous and impressive change. Having recently transi-tioned from a planned economy, the private seed industry has only recently begun to emerge and the legislation which governs it is new. Policy reform, which began in 1981, culminated in 1988 with the liberalization of input and output marketing. These changes en-gendered institutional transformation and resulted in significant development of the agricultural sector, especially rice production. Paddy output increased from 12 million tons in 1980 to 44 million tons in 2012. Since 1989, Vietnam has been a rice exporter and in 1997 the country became the second largest rice exporter in the world. Current exports average 6-7 million tons per year.